Political leadership in Turkey and Recep Tayyib Erdogan - Temiz, Suleyman; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
It examines political change in Turkey under the leadership of Recep Tayyip Erdogan during his premiership from 2002 to 2014 in order to present the portrait of Erdogan as a political leader. The interactive approach was employed to structure this analysis. In line with this approach, external and internal resources on Erdogan’s leadership are utilised. External resources are considered with regard to institutional and non institutional aspects. The non-institutional resources referred to the main characteristic of socio-economic condition of the state and relationship with the political regime and its secular representatives. With regard to internal resources of political leadership, the effects of certain life experiences on Erdogan’s politics, Islamic National Outlook policy background, major political concepts such as democracy and secularism are discussed. In addition, Erdogan's democracy conception and discourses are examined within the framework of the Justice and Development Party's conservative identity. Moreover, JDP’s policies, which emerged under Erdogan's political leadership, have been studied in the course of the transformation stages they had undergone. The political tradition of the JDP has been analysed by taking advantage of the theoretical opportunities of the centre and periphery model. Thus, Erdogan’s political leadership influence within the party and his relationship with the Justice and Development Party have been explained and analysed in the historical context.